2008
DOI: 10.1016/j.molcel.2008.08.022
|View full text |Cite
|
Sign up to set email alerts
|

Kcnq1ot1 Antisense Noncoding RNA Mediates Lineage-Specific Transcriptional Silencing through Chromatin-Level Regulation

Abstract: Recent investigations have implicated long antisense noncoding RNAs in the epigenetic regulation of chromosomal domains. Here we show that Kcnq1ot1 is an RNA polymerase II-encoded, 91 kb-long, moderately stable nuclear transcript and that its stability is important for bidirectional silencing of genes in the Kcnq1 domain. Kcnq1ot1 interacts with chromatin and with the H3K9- and H3K27-specific histone methyltransferases G9a and the PRC2 complex in a lineage-specific manner. This interaction correlates with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

20
961
2
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,103 publications
(988 citation statements)
references
References 38 publications
20
961
2
5
Order By: Relevance
“…A few dozen long noncoding RNAs (lncRNA) are known to play important regulatory roles in diverse processes, such as X inactivation (XIST) (Zhao et al 2008), imprinting (H19 and KCNQ1OT1) (Leighton et al 1995;Pandey et al 2008), and development (HOTAIR and COLDAIR) (Rinn et al 2007;Heo and Sung 2011). Recent genomic studies have shown that a substantial portion of the mammalian genome may be transcribed (Carninci et al 2005), suggesting the presence of many more noncoding transcripts and spurring efforts to catalog them (Carninci et al 2005;Harrow et al 2006) using data collected with tiling microarrays (Bertone et al 2004;Kapranov et al 2007), shotgun sequencing of expressed sequence tags (ESTs) and cloned cDNA (Carninci et al 2005;Birney et al 2007), and maps of histone modification patterns (Guttman et al 2009).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A few dozen long noncoding RNAs (lncRNA) are known to play important regulatory roles in diverse processes, such as X inactivation (XIST) (Zhao et al 2008), imprinting (H19 and KCNQ1OT1) (Leighton et al 1995;Pandey et al 2008), and development (HOTAIR and COLDAIR) (Rinn et al 2007;Heo and Sung 2011). Recent genomic studies have shown that a substantial portion of the mammalian genome may be transcribed (Carninci et al 2005), suggesting the presence of many more noncoding transcripts and spurring efforts to catalog them (Carninci et al 2005;Harrow et al 2006) using data collected with tiling microarrays (Bertone et al 2004;Kapranov et al 2007), shotgun sequencing of expressed sequence tags (ESTs) and cloned cDNA (Carninci et al 2005;Birney et al 2007), and maps of histone modification patterns (Guttman et al 2009).…”
mentioning
confidence: 99%
“…Recent work has suggested various functions and molecular mechanisms for lincRNAs (Mercer et al 2009;Ponting et al 2009), including the regulation of epigenetic marks and gene expression (Rinn et al 2007;Nagano et al 2008;Pandey et al 2008;Zhao et al 2008Zhao et al , 2010Khalil et al 2009;Koziol and Rinn 2010). Other studies have inferred and tested the functional role of lincRNAs in processes such as pluripotency and p53 response pathways by associating the expression of lincRNAs with those of protein-coding genes (Guttman et al 2009;Huarte et al 2010;Loewer et al 2010;Hung et al 2011).…”
mentioning
confidence: 99%
“…Meanwhile, a number of imprinted noncoding RNAs, such as kcnq1ot1 antisense noncoding RNA and Air noncoding RNA (12,13), were reported to participate in the developmental regulation of imprinted expression of protein-coding genes and to act on transcriptional silencing. Recent studies in Arabidopsis and rice suggest that there exist a large number of imprinted genes in plants as well (14)(15)(16)(17).…”
mentioning
confidence: 99%
“…It is also worth noting that more than 90% of all human DNA is transcribed and that the vast majority of these transcripts are of the non-proteincoding type [5], derived from antisense transcription, which is more widespread than previously believed. Importantly, antisense transcription implies the existence of nascent RNA molecules that can modify the epigenetic landscape of promoter regions, changing the DNA methylation profiles of promoters in genes with CpG canonical islands or recruiting PRC2 complexes to the vicinity of the transcription start sites (TSS) of their associated genes (e.g., Kcnq1ot1 lncRNA and the KCNQ1 gene) [6].…”
Section: Facioscapulohumeral Muscular Dystrophy (Fshd) Is a Neuromuscmentioning
confidence: 99%